2004
DOI: 10.1111/j.0904-2512.2004.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion molecules NCAM, HCAM, PECAM‐1 and ICAM‐1 in normal salivary gland tissues and salivary gland malignancies

Abstract: Immunohistochemical demonstration of NCAM, HCAM, and ICAM-1 is not related to perineural invasion or tumor behavior. PECAM-1 expression was related to vascular invasion and poor patient prognosis in three cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It has been reported that NCAM upregulation in cancer cells facilitates the migration of the cancer cells towards the nerves and promotes perineural spread in tumours including in bile duct cancer [17], gallbladder cancer [18], head and neck squamous cell carcinomas [19] and rectal cancer [20]. On the other hand, it is unlikely that NCAM plays an important role in neurotropism in tumours such as pancreatic cancer [21] or salivary gland malignancies [22]. Li et al [23] reported that NCAM expression is upregulated in nerves with PNI compared with nerves without PNI in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NCAM upregulation in cancer cells facilitates the migration of the cancer cells towards the nerves and promotes perineural spread in tumours including in bile duct cancer [17], gallbladder cancer [18], head and neck squamous cell carcinomas [19] and rectal cancer [20]. On the other hand, it is unlikely that NCAM plays an important role in neurotropism in tumours such as pancreatic cancer [21] or salivary gland malignancies [22]. Li et al [23] reported that NCAM expression is upregulated in nerves with PNI compared with nerves without PNI in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on NCAM expression in adenoid cystic carcinoma is rare. In clinical reports which can be found through Medline, the expression of NCAM in adenoid cystic carcinoma has been reported to be 89, 100, 31 and 25% (11)(12)(13)(14). Gandour-Edwards et al investigated 18 cases in which adenoid cystic carcinoma invaded the skull base.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM is expressed by peripheral nerve sheath cells and its expression has been reported in 31–100% of cases of ACC, (112115) . However, no correlation was found between the intensity of staining and either perineural invasion or recurrence (112, 114) . HCAM, PECAM-1 , and ICAM-1 have also been studied; however, no correlation was found between level of expression and invasion or recurrence in any of these molecules.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%
“…Expression patterns of HCAM and ICAM-1 were similar to those of normal salivary gland tissue; alteration in the expression of these proteins does not appear to occur with malignant transformation. One case of ACC with a poor clinical outcome showed weak PECAM-1 staining of tumor cells, but further studies are needed to elucidate the role of PECAM-1 in ACC progression (112) .…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%